Paths to positive growth in parents bereaved by drug-related death: A mixed-method study - Titlestad, Kristine Berg; Kristensen, Pål; O'Connor, Maja; Hystad, Sigurd; Dyregrov, Kari (Frontiers in Psychology, 2022)
Introduction: Drug-related deaths (DRDs) are a major public health challenge. Losing a child to a DRD can be a very stressful life event, which places parents at risk of mental and physical health problems. However, traumatic experiences like losing a child to DRD can paradoxically also lead to positive psychological changes. A mixed-method approach was used to understand the complexity of the phenomenon of post-traumatic growth experienced by parents following a DRD. Method: By combining data from a survey (n = 89) and interviews (n = 14), we explored positive growth experiences among Norwegian parents. We conducted descriptive analyses of the sample’s demographic characteristics and mean scores for Post-traumatic Growth Inventory (PTGI-SF) items. Hierarchical multiple regression was used to examine the influence of the ability to perform daily activities (WSAS), self-efficacy (GSE-SF), social support (CSS) and symptoms of prolonged grief (PG-13) on the outcome variable of post-traumatic growth (PTGI-SF). Reflexive thematic analysis was applied to analyze the qualitative data. Finally, we integrated the results of the survey and the interviews. Results: For items measuring post-traumatic growth, parents scored highest on the item “I discovered that I’m stronger than I thought I was” and lowest on the item “I am able to do better things with my life”. Self-efficacy and social support had a statistically significant relation with post-traumatic growth. Two themes were generated from the interviews: (I) new perspectives on life; and (II) new paths in life. Even though the “New Possibilities” subscale had the lowest mean score for the PTGI-SF, new paths in life were important for many of the interviewed parents. Discussion: Parents described traumatic stressors associated with having a child who uses narcotics and hence experienced positive changes even before losing their child. We argue that on an individual level, the consequences of spillover stigma, low self-efficacy and intrusive rumination can hinder potential post-traumatic growth. On a group level, enhancing network support may increase post-traumatic growth experiences. Hence, parents who have experienced a DRD can benefit from help to activate their social networks and strengthen their self-efficacy.